Growth, yield attributes and seed yield of pre-release genotypes of castor (Ricinus communis L.) as influenced by fertilizer levels under rainfed conditions of central dry zone of Karnataka: GROWTH AND YIELD OF CASTOR AS INFLUENCED BY FERTILIZER LEVELS - V VENKATACHALAPATHI; T RUDRAMUNI; K T RAJENDRA PRASAD; SHARANAPPA JANGANDI (Journal of Oilseeds Research, 2016)
An experiment was conducted to assess the response of castor genotypes in relation to fertilizer input. Three genotypes of castor (SHB-872, RHC-277 and JC-12) were tried under four fertilizer levels i.e., control (no fertilizer), 50%, 100% and 150% recommended dose of fertilizer (RDF) under rainfed conditions during kharif season 2011 on black soils at Zonal Agricultural Research Station, Babbur Farm, Hiriyur, Karnataka. The study revealed that there was a linear response to graded levels of fertilizer. Significantly higher seed yield of castor (2302 kg/ha) was registered at 150% RDF. Among castor genotypes, JC-12 recorded the significantly higher seed yield (2103 kg/ha), however, it was comparable with that of SHB-872 (1981 kg/ha) and RHC-277 (1967 kg/ha). Economic analysis revealed that genotype JC-12 gave higher gross returns (` 75718/ha), net returns (` 57407/ha) and B:C ratio (4.12). Among fertilizer doses, application of 150% RDF accrued higher gross returns (` 82898/ha), net returns (`63962/ha) and BC ratio (4.63).